Hoarding knowledge or hoarding stress? Investigating the link between digital hoarding and cognitive failures among Chinese college students - Liu, Yan; Liu, Yaorong (Frontiers in Psychology, 2025)
IntroductionDigital hoarding is defined as the persistent accumulation of digital content and an unwillingness to delete it. This behavior has been found to be particularly prevalent among young people. This study aims to explore the impact of digital hoarding on cognitive failures, examining fatigue as a mediator and mindfulness as a moderator.MethodA total of 801 participants were recruited to complete a survey that contained measures of digital hoarding, fatigue, mindfulness, and cognitive failures. The hypothesized moderated mediation model was tested using Models 4 and 8 from the PROCESS macro in SPSS.Results(1) Digital hoarding positively predicted cognitive failures. (2) Fatigue mediated the relationship between digital hoarding and cognitive failures. (3) Mindfulness moderated both the direct effect of digital hoarding on cognitive failures and the first segment of the mediating role of fatigue.DiscussionThis study contributes to a deeper understanding of digital hoarding. It also highlights the great potential of mindfulness in mitigating the negative effects of digital hoarding, and provides students with practical strategies for developing healthier and more balanced digital habits.